Transcriptome data from four stages of carpel development in Eschscholzia californica and Solanum lycopersicum - Kong, Doudou; Justus Liebig University Giessen (My University, 2025)
This dataset contains transcriptome data from four stages of carpel development in Eschscholzia californica and Solanum lycopersicum. A detailed description of the dataset can be found in the files “dataset_description.docx” or “dataset_description.pdf”.
Keywords: ddc:580